2007
DOI: 10.1016/j.neuroimage.2006.10.045
|View full text |Cite
|
Sign up to set email alerts
|

Prospective reports of chronic life stress predict decreased grey matter volume in the hippocampus

Abstract: Chronic stress in non-human animals decreases the volume of the hippocampus, a brain region that supports learning and memory and that regulates neuroendocrine activity. In humans with stressrelated psychiatric syndromes characterized by impaired learning and memory and dysregulated neuroendocrine activity, surrogate and retrospective indicators of chronic stress are also associated with decreased hippocampal volume. However, it is unknown whether chronic stress is associated with decreased hippocampal volume … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
227
4
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 283 publications
(249 citation statements)
references
References 74 publications
17
227
4
1
Order By: Relevance
“…Although population research has established robust effects of poverty and inequality on these outcomes (37)(38)(39)(40)(41)(42), neural mechanisms of these effects have not been a primary focus in population approaches. However, within neuroscience and health psychology, research has begun to show that early life experiences such as parenting and SES have effects on brain areas such as the amygdala and prefrontal cortex (43)(44)(45)(46)(47), areas that have also been linked to a variety of relevant outcomes such as crime and violence (48,49), depression (50), social cognition (51,52), drug use (53,54), and cognitive control (55). For example, a recent study demonstrated that early life stress predicted stress responses in the hypothalamicpituitary-adrenal axis, which in turn predicted connectivity between the amygdala and prefrontal cortex and later risk for depression (56).…”
Section: Current Practices In Neuroimagingmentioning
confidence: 99%
See 1 more Smart Citation
“…Although population research has established robust effects of poverty and inequality on these outcomes (37)(38)(39)(40)(41)(42), neural mechanisms of these effects have not been a primary focus in population approaches. However, within neuroscience and health psychology, research has begun to show that early life experiences such as parenting and SES have effects on brain areas such as the amygdala and prefrontal cortex (43)(44)(45)(46)(47), areas that have also been linked to a variety of relevant outcomes such as crime and violence (48,49), depression (50), social cognition (51,52), drug use (53,54), and cognitive control (55). For example, a recent study demonstrated that early life stress predicted stress responses in the hypothalamicpituitary-adrenal axis, which in turn predicted connectivity between the amygdala and prefrontal cortex and later risk for depression (56).…”
Section: Current Practices In Neuroimagingmentioning
confidence: 99%
“…For example, longitudinal neuroimaging of representative samples, with repeat scans starting early and continuing across development, will advance developmental science, as well as our broad understanding of brain plasticity and relationship to experience (12,18,61,122). Sociologists and social psychologists will also have a major stake in this research and will be particularly important in helping to formulate the possible chronic influences on brain structure and function, such as discrimination, poverty, SES, and social support (5,17,43,44). As well, these influences of brain function and structure may act as moderators of brain-behavior relationships, thus leading to a more dynamic model of social context, brain function, and behavior.…”
Section: )mentioning
confidence: 99%
“…To date, few studies have examined the association between life stress and brain structure in adult participants without a history of psychopathology or brain disorder. [3][4][5][6] Moreover, individuals recruited for previous studies had experienced different types of stress-related events, including illness or injury, death of a close friend or relative, unemployment and the ending of important relationships, which might have variable effects on the brain. 6 Furthermore, the findings from these studies indicated that grey matter atrophy could only be observed 3 months after stressful life events.…”
Section: Introductionmentioning
confidence: 99%
“…While many have reported volumetric reductions in the hippocampus [15][16][17] or amygdala [18], others have found no change in either hippocampal or amygdala volume [19,20]. Resting-state functional imaging studies have also produced varied results, with some research reporting increased amygdala-hippocampal connectivity associated with greater levels of self-reported trauma symptoms [21] or following stress induction [22], and other work reporting no trauma-related connectivity changes [18].…”
Section: Introductionmentioning
confidence: 99%